Análise da vulnerabilidade à degradação dos solos da vertente úmida do Maciço de Uruburetama/Ce - Freires, Eduardo Viana (2020)
The various interventions processed over the years in the Massif of Uruburetama / CE compromise environmental and agricultural sustainability. The physical characteristics of the area favor erosive processes and gravitational movements, which are enhanced by human activities and result in soil degradation. In view of the above, this research aimed to assess and spatialize the vulnerability to soil degradation in the wet slope of the Massif using geoprocessing and geotechnical techniques, in order to support environmental management and planning. As an evaluation support, orbital images were used, 184 soil samples, which were subjected to laboratory analysis according to ABNT Solos norms, pluviometric records of FUNCEME stations and field observations. The research was organized in the following stages: socio-environmental analysis, in which we sought to understand the physical and human condition, identifying the influence of interventions to trigger mass movement and accelerate erosion processes; comparison between cover and land use mapping obtained by supervised classification of OLI / Landsat-8 and MSI / Sentinel 2 images; analysis of natural vulnerability to soil degradation based on geomorphometric variables extracted from MDE ALOS PALSAR; automatic extraction of structural lineaments from the ALOS PALSAR image, which allowed analyzing the influence they exert on the triggering of gravitational movements; Environmental vulnerability analysis to soil degradation based on multicriteria analysis, in a GIS environment, involving the variables coverage and land use, natural vulnerability to soil degradation, lineament density, erodibility, obtained from the results of the analysis of the samples of collected soils (granulometry, structure, organic matter, permeability), and erosivity, calculated through rainfall records obtained over a 10-year interval (2010-2019). The results show that the expansion of the urban network and the cultivation areas occur indiscriminately in areas of permanent preservation, disregarding the legal requirements, although all the municipalities analyzed have an environmental management body, and that some have laws that regulate the use and occupation of the land. ground. The mapping of land cover and use made it possible to understand the level of interventions and alteration of the landscape in the massif and the better quality of the product generated from the MSI / Sentinel 2 image compared to OLI / Landsat-8. The natural vulnerability map indicates that the classes of high and very high vulnerability are mainly located on the eastern, northern and northeastern slopes of the massif. The predominant distribution, density and orientation of structural lineaments may indicate susceptibility to the occurrence of mass movement, provided that it considers the dominant physical characteristics and the degree of human intervention on the slopes. The environmental vulnerability map indicates that the classes of least vulnerability are associated with altimetric levels between 600 and 1000m, and with sectors of the hinterland depression. The upper and very upper classes are widely disseminated on the slopes of the mountains and are due mainly to the strong intervention promoted by agricultural activity. The generated cartographic products are instruments to support environmental management and planning, both for monitoring and for indications of land use and occupation.